Effect of diuretics on kidney stone-forming risk – an investigation using multiple timed urine collections - Morley, Julia; Rensburg, Megan; Hoffman, Mariza; Hassan, Mogamat Shafick; Davids, Mogamat Razeen (African Journal of Nephrology, 2022)
Introduction: Thiazide diuretics can lower urinary calcium excretion, helping to prevent recurrent calcium kidney stones. As dietary intake and urine chemistry varies throughout the day, a 24-h urine collection may not provide sufficient information to guide the optimal management in individual patients. Using multiple timed urine collections, we sought to identify times during the day when stone-forming risk is higher, allowing for therapy to be more accurately targeted. Methods: In a prospective study, healthy adult volunteers took a 4-week course of either hydrochlorothiazide (HCTZ) 25 mg/d or indapamide 2.5 mg/d. They were assessed at baseline, and at days 7, 14 and 28. At each time point, blood samples were taken for analysis and multiple timed urine samples were collected throughout the day, together with one overnight sample. Results: Diuretic treatment was well tolerated. Daily calcium and citrate excretion decreased, while ionized calcium and phosphate excretion were unchanged. Ionized calcium-divalent phosphate and ionized calcium-oxalate products were unchanged. In the timed urine samples, calcium excretion was decreased, particularly by indapamide, in the morning. Indapamide, but not HCTZ, decreased urinary citrate excretion, most obviously in overnight and early morning urines. No changes in ionized calcium were observed. Decreased divalent phosphate excretion was observed at several time points in the indapamide group. The ionized calcium-divalent phosphate product tended to decrease at most time points in both groups but no significant changes were observed in the ionized calcium-oxalate product. Conclusions: Indapamide 2.5 mg/d has a stronger protective effect against forming calcium kidney stones than HCTZ 25 mg/d. Most of the benefits appear to be achieved during the daytime and it may therefore be beneficial to prescribe medication twice daily or in the evening to maximize the protective effects of these agents. The benefits of indapamide treatment were attenuated by a reduction in urinary citrate excretion, an effect which has not been previously described.